Physicochemical Characterization of Indonesian Natural Clay from Hutumuri, Ambon City, Indonesia as a Low-Cost Porous Material - H. Tehubijuluw; E. K. Huliselan; R. Subagyo; R. E. Nugraha; A. A. Jalil; I. W. Sutapa; Rahayu; D. Sri; N.F. Jaafar (Faculty Mathematics and Natural Sciences, Halu Oleo University, 2026)
Natural clays are widely explored as low-cost and sustainable alternatives to synthetic porous materials due to their abundance, structural versatility, and potential for environmental applications. In this study, natural zeolite obtained from Hutumuri Village, Ambon, Indonesia, referred to as Hutumuri Natural Clay (HNC), was prepared and characterized to evaluate its physicochemical properties. The raw material underwent purification, particle size reduction (<2 µm), and chemical activation using hydrochloric acid. Comprehensive characterization was carried out using X-ray fluorescence (XRF), X-ray diffraction (XRD), energy-dispersive X-ray spectroscopy (EDX), Fourier-transform infrared spectroscopy (FTIR), and Brunauer–Emmett–Teller (BET) surface area analysis. The results revealed that HNC contains high levels of SiO2 and Al2O3, with a Si/Al ratio of 1.1, classifying it as a low-silica zeolite. XRD analysis confirmed quartz as the dominant phase, while FTIR and EDX results supported the presence of silicate, aluminate, and ferrite species. BET analysis showed a surface area of 86.002 m2/g with an average pore diameter of 7.032 nm, indicating mesoporous characteristics. These properties suggest that HNC is a promising candidate for applications in adsorption, catalysis, and other environmental remediation processes.